2021
DOI: 10.48550/arxiv.2103.09632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inferred vs traditional personality assessment: are we predicting the same thing?

Pavel Novikov,
Larisa Mararitsa,
Victor Nozdrachev

Abstract: Machine learning methods are widely used by researchers to predict psychological characteristics from digital records. To answer whether automatic personality estimates retain the properties of the original traits, we reviewed 220 recent articles.First, we put together the predictive quality estimates from a subset of the studies which declare separation of training, validation, and testing phases, which is critical for ensuring the correctness of quality estimates in machine learning (Hastie et al. (2009); Zh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 96 publications
(139 reference statements)
1
11
0
Order By: Relevance
“…The second baseline uses 145 features (NETSENSE) and 2212 features (NETHEALTH) self-reported in the surveys: grades, health, happiness, activity, book reading, and club membership. These are highly personal and sensitive features, and have been shown to be the upper bound of automatic personality traits prediction [40]. We find our method to outperform the first baseline and, surprisingly, very competitive with respect to the prediction upper-bound.…”
Section: A the Netsense And Nethealth Studiesmentioning
confidence: 69%
See 1 more Smart Citation
“…The second baseline uses 145 features (NETSENSE) and 2212 features (NETHEALTH) self-reported in the surveys: grades, health, happiness, activity, book reading, and club membership. These are highly personal and sensitive features, and have been shown to be the upper bound of automatic personality traits prediction [40]. We find our method to outperform the first baseline and, surprisingly, very competitive with respect to the prediction upper-bound.…”
Section: A the Netsense And Nethealth Studiesmentioning
confidence: 69%
“…We also test combinations of feature sets. The red area shows the credible upper limits for correlations between predicted and self-reported personality traits [40].…”
Section: B Inferring Psychometric Traits 1) Predictive Setupmentioning
confidence: 99%
“…Because automatic personality recognition approaches are inherently data-driven, the availability of experimental datasets plays a crucial role. According to Novikov et al [83], more than 40% of studies on personality involve the collection of new datasets that remain private. The remaining studies rely on a few shared and reusable datasets.…”
Section: Personality Datasetsmentioning
confidence: 99%
“…40. In a survey of over 200 papers on personality published since 2017, Novikov et al [83] found that the reported Pearson correlation coefficients 15…”
Section: Evaluation Metricsmentioning
confidence: 99%
See 1 more Smart Citation